Postać Atanazego Brzeskiego w świetle jego Diariusza. Próba interpretacji - Gołębiowski, Michał (Tematy i Konteksty, 2016)
The short study is devoted to the person of Athanasius of Brest, one of the most prominent Orthodox priests and religious activists of the 17th century, seen in the light of his only work, Diary (Дыярыуш, 1646). The paper attempts to analyse Athanasius’ dis-uniate mission as a consequence of his own prophetic creation, belief in supernatural visions and radical passion for the Orthodox traditionalism, described in his book. It appears that the key place in the work of Athanasius is occupied by the Icon of Virgin Mary of Kupiatycze, the sacred image regarded by the monk not only as a source of grace for his Apostolic ministry, but also as a sign of the real identity of the Orthodox Church. Athanasius’ social activity turns out to be important for understanding the controversies surrounding the Union of Brest.